Derajat kontaminasi SARS-CoV-2 pada lingkungan di Rumah Sakit Universitas Mataram - Bayu Tirta Dirja (Unram Medical Journal, 2022)
Since 2019, SARS-COV2 has become a global pandemic. Many hospitals has become designated hostilas for the treatment of SARS-COV2 patients. As part of preventive measures, hospitals are required to conduct routine desinfection procedure to minimize the risk of virus transmission. Therefore this study aims to evaluate surface contamination of SARS COV2 at the emergency ward, outpatients SARS COV2 ward and inpatient ward for SARS-COV2 in how hospital. Surface samples were collected for viral RNA detection 5 hours post decontamination. Detection for SARS-COV2 was performed with quantitative reverse transcription polymerase chain reactin. As many as 18 sampels were collected on October 2021. No samples were detected for the trace of SARS-COV2. Hence this could suggests that sufficient decontamination and preventive measures conducted by healthcare workers were established in our hospital.